International myeloma working group consensus statement and guidelines regarding the current role of imaging techniques in the diagnosis and monitoring of multiple Myeloma - Dimopoulos, M.; Terpos, E.; Comenzo, R.L.; Tosi, P.; Beksac, M.; Sezer, O.; Siegel, D.; Lokhorst, H.; Kumar, S.; Rajkumar, S.V.; Niesvizky, R.; Moulopoulos, L.A.; et al. (Leukemia, 2009)
Several imaging technologies are used for the diagnosis and management of patients with multiple myeloma (MM). Conventional radiography, computed tomography (CT), magnetic resonance imaging (MRI) and nuclear medicine imaging are all used in an attempt to better clarify the extent of bone disease and soft tissue disease in MM. This review summarizes all available data in the literature and provides recommendations for the use of each of the technologies. Conventional radiography still remains the 'gold standard' of the staging procedure of newly diagnosed and relapsed myeloma patients. MRI gives information complementary to skeletal survey and is recommended in MM patients with normal conventional radiography and in all patients with an apparently solitary plasmacytoma of bone. Urgent MRI or CT (if MRI is not available) is the diagnostic procedure of choice to assess suspected cord compression. Bone scintigraphy has no place in the routine staging of myeloma, whereas sequential dual-energy X-ray absorptiometry scans are not recommended. Positron emission tomography/CT or MIBI imaging are also not recommended for routine use in the management of myeloma patients, although both techniques may be useful in selected cases that warrant clarification of previous imaging findings, but such an approach should ideally be made within the context of a clinical trial. © 2009 Macmillan Publishers Limited All rights reserved.
Keywords: Computed tomography; Conventional radiography; Magnetic Resonance Imaging; multiple myeloma; Nuclear medicine imaging